2015
DOI: 10.1186/s12891-015-0718-8
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of CDAI and SDAI indices in comparison to DAS-28 index in Moroccan patients with rheumatoid arthritis

Abstract: BackgroundClinical disease activity index (CDAI) and simplified disease activity index (SDAI) are useful tools for the evaluation of disease activity in patients with rheumatoid arthritis (RA), but have not been comparatively validated in Moroccan population. Therefore, this study was designed to assess validity and reliability of CDAI and SDAI in comparison to disease activity score-28 joints (DAS-28) in Moroccan patients with RA.MethodsPatients with RA were included in a cross-sectional study. Patient charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 12 publications
2
17
1
Order By: Relevance
“…This study assessed the correlation and concordance of the different clinimetric indices in a cohort of Latin American mestizo patients with early RA from two reference centers in northwestern Colombia. Most of the patients who entered the study were women under DMARDs treatment and had normal APRs, an overall good perception of patient's general condition and low joint count, contrary to what was found in clinimetric studies in Europe, Brazil and Morocco, and similar to that found in the cohort of Mierau et al . where 50–67% of patients were in remission or low disease activity.…”
Section: Discussioncontrasting
confidence: 46%
“…This study assessed the correlation and concordance of the different clinimetric indices in a cohort of Latin American mestizo patients with early RA from two reference centers in northwestern Colombia. Most of the patients who entered the study were women under DMARDs treatment and had normal APRs, an overall good perception of patient's general condition and low joint count, contrary to what was found in clinimetric studies in Europe, Brazil and Morocco, and similar to that found in the cohort of Mierau et al . where 50–67% of patients were in remission or low disease activity.…”
Section: Discussioncontrasting
confidence: 46%
“…The other scoring systems for assessing RA disease activity include the clinical disease activity index (CDAI) and simplified disease activity index (SDAI). Specificity and sensitivity for CDAI ( P value < 0.001; 95% confidence interval (CI) 94.2–98.1) showed 85.3% and 97% respectively and those for SDAI ( P value < 0.001; 95% CI 87.5–94.18) showed 62.2% and 97.6% [ 35 ]. RA patients diagnosed with depression have reduced rates of clinically significant RA remission, increased pain, worse function and quality of life and increased mortality [ 26 , 36 ].…”
Section: Mental Health Disorders and Ramentioning
confidence: 99%
“…It consisted of 12 items that assessed the symptoms, functional limitation, and environmental factors related to dry eye [33], with an overall score of 0-100. e severity of ocular surface diseases assessed by OSDI was graded as follows: 0-12: normal; 13-22: mild; 23-32: moderate; 33-100: heavy [34]. Another survey used to assess the rheumatoid arthritis was the disease activity questionnaire (DAS-28) [35], which evaluated the number of tender and swollen joints (28-joints count), selfassessment of disease activity of the patients, and erythrocyte sedimentation rate (ESR) [36]. According to the OSDI, the patients were graded into the symptomatic group (score-≥ 12) and the asymptomatic group (score < 12).…”
Section: Patientsmentioning
confidence: 99%